2008
DOI: 10.1080/03650340801998623
|View full text |Cite
|
Sign up to set email alerts
|

Plant density and nitrogen effects on growth dynamics, light interception and yield of maize

Abstract: Maize (Zea mays L.) growth and yield are most sensitive to variations in plant density and nitrogen (N) in north-western Pakistan. This study was conducted on the Agricultural Research Farm of NWFP (North West Frontier Province) Agricultural University, Peshawar, from 2002-2004 to establish an accurate plant density and N management system aimed at high yield of maize. The 2 6 3 6 6 factorial experiment was designed having two plant densities (P1 ¼ 60,000 and P2 ¼ 100,000 plants ha 71 ) and three nitrogen rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…The increase in NR and VCR with application of 100 and 150 kg N ha 1 was attributed to faster CGR, improvement in grain yield and yield components (unpublished data). Similarly, in the previous research, an increase in NR with more N (120 and 180 kg N ha 1 ) than 60 kg N ha 1 was attributed to an increase in LAI, CGR, number of grains ear -1 , ears 100 plants -1 , and grain yield (Amanullah et al, 2007;Amanullah and Khalil, 2009;Amanullah and Shah, 2010;Khan et al, 2008). Greater NR of 32 and 85 USD ha 1 with application of greater N rates of 112 and 224 kg N ha 1 , respectively, was obtained as compared with the check (N applied) and the lower rate of 56 kg N ha 1 (Stanger et al, 2008).…”
Section: N Rates Genotypessupporting
confidence: 58%
See 1 more Smart Citation
“…The increase in NR and VCR with application of 100 and 150 kg N ha 1 was attributed to faster CGR, improvement in grain yield and yield components (unpublished data). Similarly, in the previous research, an increase in NR with more N (120 and 180 kg N ha 1 ) than 60 kg N ha 1 was attributed to an increase in LAI, CGR, number of grains ear -1 , ears 100 plants -1 , and grain yield (Amanullah et al, 2007;Amanullah and Khalil, 2009;Amanullah and Shah, 2010;Khan et al, 2008). Greater NR of 32 and 85 USD ha 1 with application of greater N rates of 112 and 224 kg N ha 1 , respectively, was obtained as compared with the check (N applied) and the lower rate of 56 kg N ha 1 (Stanger et al, 2008).…”
Section: N Rates Genotypessupporting
confidence: 58%
“…In both years, the grain yield increased with the increase in N to 150 kg N ha 1 but a further increase in N at 200 kg ha 1 did not increase the grain yield (Table 2). Our previously published research indicated that on N-deficient soils of Peshawar, grain yield in maize increased with the application of more N (120 and 180 kg ha 1 ) over only 60 kg N ha 1 because of increase in LAI (Amanullah et al, 2007), light interception (Khan et al, 2008), number of ears 100 plants -1 , and 1000-grain weight (Amanullah and Shah, 2010), and increase in dry matter partitioning (Amanullah and Shah, 2011). Application of CAN and AS resulted in more grain yield than did urea in Year 1; however, no significant differences in grain yield were observed while using different N fertilizer sources in Year 2 (Table 2).…”
Section: Grain Yieldmentioning
confidence: 99%
“…Increase in maize productivity with nitrogen fertilization was also reported by many workers (Malaiya et al, 2004; Amanullah et al, 2009a, 2015b). The increase in yield and yield components in the current study with N supply probably may be due to the increase in light interception (Amanullah et al, 2008) because of it higher LAI (Amanullah et al, 2014). Many researchers reported improvement in maize yield and yield components while increasing N level.…”
Section: Discussionmentioning
confidence: 76%
“…According to Guo et al (2016), N is the most yield-restraining nutrient in crop production globally. Our previous research work on maize and nitrogen management revealed that proper nitrogen rates and nitrogen timings (splits) management improve maize growth and development (Amanullah et al, 2007, 2008, 2009a,b; Amanullah and Shah, 2010), yield and yield components (Amanullah et al, 2009a), grain quality (Amanullah et al, 2010), and growers income (Amanullah et al, 2010) in the study area. In another study (Amanullah et al, 2015b), we noticed that the integrated use of nitrogen (120 or 150 kg N ha −1 ) along with compost (2 t ha −1 ) improved yield and yield components in maize under deep (45 cm) than shallow (15 cm) tillage system under semiarid climate.…”
Section: Introductionmentioning
confidence: 90%
“…It was studied by Yin et al (2011), that corn yield was increased significantly as the plant height increased and also demonstrated by Katsvairo et al (2003), that plant yield is increased with increment in plant height. Many studies on plant height and biomass accumulation revealed that plant height is positively correlated with biomass accumulation (Amanullah et al, 2008;Greef et al, 1999;Hamid & Nasab, 2001). Similarly, in this experiment, an increase in nitrogen rate had significantly increased the plant height (Figure 2) (Ahmadi, 2010;Islam et al, 2018); thus, it had increased the biomass accumulation (Figure 3) (Mahipat & Mukesh, 2014).…”
Section: Plant Height and Biomass Accumulationmentioning
confidence: 99%